2020
DOI: 10.1080/03091929.2020.1756283
|View full text |Cite
|
Sign up to set email alerts
|

Stability and evolution of two opposite-signed quasi-geostrophic shallow-water vortex patches

Abstract: We examine the equilibrium forms, linear stability and nonlinear evolution of two patches having oppositesigned, uniform potential vorticity anomalies in a single-layer shallow-water flow, under the quasi-geostrophic approximation. We widely vary the vortex area ratio, the potential vorticity anomaly ratio, as well as the Rossby deformation length to unravel the full complexity of possible interactions in this system. Oppositesigned vortex interactions turn out to be far richer than their like-signed counterpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Supplementary movie 1 available at shows the full evolution of the modon for the case depicted in figure 5. A similar breakdown due to asymmetric instability is observed by Makarov & Kizner (2011) and Jalali & Dritschel (2020) for the case of oppositely signed vortex patches.
Figure 5.Plots of the surface buoyancy for and ( a ) , ( b ) , ( c ) , ( d ) , ( e ) , and ( f ) .
…”
Section: Vortex Breakdownsupporting
confidence: 82%
See 1 more Smart Citation
“…Supplementary movie 1 available at shows the full evolution of the modon for the case depicted in figure 5. A similar breakdown due to asymmetric instability is observed by Makarov & Kizner (2011) and Jalali & Dritschel (2020) for the case of oppositely signed vortex patches.
Figure 5.Plots of the surface buoyancy for and ( a ) , ( b ) , ( c ) , ( d ) , ( e ) , and ( f ) .
…”
Section: Vortex Breakdownsupporting
confidence: 82%
“…Supplementary movie 1 available at https://doi.org/10.1017/jfm.2023.607 shows the full evolution of the modon for the case λ = 0.8 depicted in figure 5. A similar breakdown due to asymmetric instability is observed by Makarov & Kizner (2011) and Jalali & Dritschel (2020) for the case of oppositely signed vortex patches. Snyder et al (2007) considered the evolution of SQG modons in a primitive equation model and observed that waves could form within the modon.…”
Section: Vortex Breakdownsupporting
confidence: 76%
“…For QGSW equations, there are some numerical stability results [30,23], but there seem to be very few results on mathematical stability. However, due to the special energy characteristics of our constructed solution, we can prove its orbital stability.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Most previous studies have focused on symmetric merging of two identical vortices or, to a lesser extent, asymmetric merging with a few examples of different strength ratios, see, among others, Melander, Zabusky & McWilliams (1988), Meunier et al (2002) and Dritschel (1995). In two recent studies by Jalali & Dritschel (2018, 2020 the general inviscid interactions of vortex patches are studied with many examples over a wide parameter space, including the ratio of sizes and vorticity. Our study is not the first that attempts to describe all interaction scenarios in terms of different flow regimes.…”
Section: Discussionmentioning
confidence: 99%